Effect of a corticotropin releasing hormone receptor antagonist on colonic sensory and motor function in patients with irritable bowel syndrome. Issue 7 (11th June 2004) - Sagami, Y; Shimada, Y; Tayama, J; Nomura, T; Satake, M; Endo, Y; Shoji, T; Karahashi, K; Hongo, M; Fukudo, S
Abstract : Background and aims: Corticotropin releasing hormone (CRH) is a major mediator of the stress response in the brain-gut axis. Irritable bowel syndrome (IBS) is presumed to be a disorder of the brain-gut link associated with an exaggerated response to stress. We hypothesised that peripheral administration of α-helical CRH (αhCRH), a non-selective CRH receptor antagonist, would improve gastrointestinal motility, visceral perception, and negative mood in response to gut stimulation in IBS patients. Methods: Ten normal healthy subjects and 10 IBS patients, diagnosed according to the Rome II criteria, were studied. The tone of the descending colon and intraluminal pressure of the sigmoid colon were measured at baseline, during rectal electrical stimulation (ES), and at recovery after administration of saline. Visceral perception after colonic distension or rectal ES was evaluated as threshold values on an ordinate scale. The same measurements were repeated after administration of αhCRH (10 μg/kg). Results: ES induced significantly higher motility indices of the colon in IBS patients compared with controls. This response was significantly suppressed in IBS patients but not in controls after administration of αhCRH. Administration of αhCRH induced a significant increase in the barostat bag volume of controls but not in that of IBS patients. αhCRH significantly reduced the ordinate scale of abdominal pain and anxiety evoked by ES in IBS patients. Plasma adrenocorticotropic hormone and serum cortisol levels were generally not suppressed by αhCRH. Conclusion: Peripheral administration of αhCRH improves gastrointestinal motility, visceral perception, and negative mood in response to gut stimulation, without affecting the hypothalamo-pituitary-adrenal axis in IBS patients.